Upaya Meningkatkan Kemampuan Siswa Dalam Mengerjakan Soal Cerita Pada Mata Pelajaran Matematika Melalui Metode Bermain Kartu Soal Bagi Siswa Kelas VI SD - Watha Watha (Jurnal Riset Teknologi dan Inovasi Pendidikan (Jartika), 2019)
This classroom action research aims to describe an increase in the ability to do story problems in mathematics through card games for class VI of Elementary School. Conducted in two cycles with data collection methods through observation, interviews, documentation, and test. The results of the study before the action were held at 5.97 and after the action was taken to be 6.65 thus means there was an increase in achievement of 0.68. So it was concluded that there was an increase in learning achievement of class VI students at Elementary School in working on story problems in mathematics through card games.